DNA redox modulations and global DNA methylation in bipolar disorder: Effects of sex, smoking and illness state. (March 2018) - Ceylan, Deniz; Scola, Gustavo; Tunca, Zeliha; Isaacs-Trepanier, Cameron; Can, Güneş; Andreazza, Ana C.; Young, L. Trevor; Özerdem, Ayşegül
Abstract: DNA redox modulations and methylation have been associated with bipolar disorder (BD) pathophysiology. We aimed to investigate DNA redox modulation and global DNA methylation and demethylation levels in patients with BD during euthymia, mania or depression in comparison to non-psychiatric controls. The roles of sex and smoking as susceptibility factors for DNA redox modulations and global DNA methylation and demethylation were also explored. Levels of 5-methylcytosine (5-mC), 5-hydroxymethylcytosine (5-hmC) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) were assessed in DNA samples of 75 patients with DSM-IV BD type I (37 euthymic, 18 manic, 20 depressive) in comparison to 60 non-psychiatric controls. Levels of 5-mC and 5-hmC were assessed using Dot Blot as a screening process, and verified using ELISA. Levels of 8-OHdG were assessed using ELISA. The levels of 8-OHdG significantly differed among non-psychiatric control, euthymia, mania and depression groups [ F (3, 110) = 2.771, p = 0.046], whereas there were no alterations in the levels of 5-hmC and 5-mC. Linear regression analyses revealed the significant effects of smoking ( p = 0.031) and sex ( p = 0.012) as well as state of illness on the levels of 8-OHdG ( p = 0.025) in patients with BD. Our results suggest that levels of 8-OHdG may be affected by sex, illness states and smoking in BD. Highlights: Global DNA methylation and hydroxymetylation did not show differences between patients with BD and non-psychiatric controls. There was an alteration in the levels of 8-OHdG among non-psychiatric controls, euthymic, depressive and manic patients. Female patients, but not male, with BD demonstrated to have higher levels of 8-OHdG when compared to non-psychiatric counterpartsb. State of illness, female sex and smoking are the factors associated with the levels of 8-OHdG in BD.